2019
DOI: 10.3390/rs11161859
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Soil and Crop Segmentation from Remotely Sensed Data

Abstract: One of the most challenging problems in precision agriculture is to correctly identify and separate crops from the soil. Current precision farming algorithms based on artificially intelligent networks use multi-spectral or hyper-spectral data to derive radiometric indices that guide the operational management of agricultural complexes. Deep learning applications using these big data require sensitive filtering of raw data to effectively drive their hidden layer neural network architectures. Threshold technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…The method achieved an average accuracy of 92%. Others have used machine learning methods for plot segmentation, and classification [23,24]. All of these methods require training stages that limit real-time functionality.…”
Section: Introductionmentioning
confidence: 99%
“…The method achieved an average accuracy of 92%. Others have used machine learning methods for plot segmentation, and classification [23,24]. All of these methods require training stages that limit real-time functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, machine learning algorithms have been used for different remote sensing applications [14][15][16][17][18]. Algorithms like artificial neural networks (ANN), support vector machine (SVM), decision trees (DT), random forests (RF), and others are powerful tools in assisting in UAV-based image analysis [19].…”
Section: Introductionmentioning
confidence: 99%
“…This could be more pronounced in plots with fewer rows. Recent studies have demonstrated the possibility to improve the segmentation of plant-soil pixels, e.g., using Support Vector Machine (SVM) classification or Convolutional Neural Networks [27,33,34]; (ii) aerial-based sensing has an advantage over ground-based sensing platforms in generating surface maps in real time and measuring plant parameters from a large number of plots at a time, typically associated with the time required to make ground-based measurements in large trials [12,13]; (iii) using high-resolution and low-altitude UAVs can overcome further limitations of ground-based sensing platforms, such as the non-simultaneous measurement of different plots, trafficability, row, and plot geometries requiring specific sensor configurations, and vibrations resulting from uneven field surfaces [12,28]. Given that the operation of UAV image acquisition is less labor-intensive, and owing to improved segmentation procedures and a higher precision than non-imaging proximal sensing, aerial-based multispectral sensing via UAV is expected to increase the efficiency of high-throughput phenotyping in large-scale plant breeding programs [10,12].…”
Section: Heritability Of Spectral Indices In Different Row Variantsmentioning
confidence: 99%